Profile of Leprosy Patients at the Dermatology and Venereology Polyclinic of Dr. M. Djamil Padang Hospital in 2018-2021 - Habib El Binampiy Busnia; Gustia Rina; Deddy Herman (International Journal of Health and Medicine, 2024)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that attacks several parts of the body, especially the upper respiratory tract, skin, and peripheral nerves. Indonesia is the third country with the most leprosy in the world. This study aims to determine the profile of leprosy patients at the Dermatology and Venereology Polyclinic Dr. M. Djamil Padang Hospital in 2018-2021. This research is descriptive retrospective with total sampling technique using secondary data in the form of medical records. The sample of this study were all leprosy patients in 2018-2021 who were fulfilled inclusion criteria, with a total of 39 patients. The results showed that the most age group was >14 years (100%), the most gender was male (74.36%), the most residence was Padang (33.33%), and almost all leprosy patients (92.31%) had no history of household contact with leprosy patients. Most of the leprosy patients were of the multibacillary type (74.36%) with positive smear results (46.15%), without leprosy reaction (61.54%), and the most disability level that occurred was grade 0 disability (48.72%). The conclusion of this study is that most cases of leprosy at the Dermatology and Venereology Polyclinic RSUP Dr. M. Djamil Padang in 2018-2021 aged >14 years, male, having address in Padang City, had no history household contact, multibacillary type, positive smear result, without reaction, and level 0 disability.